2016
DOI: 10.9790/3013-068012629
|View full text |Cite
|
Sign up to set email alerts
|

Blindness and ocular posterior segment involvement in the acute phase of Kawasaki disease: a mini-review

Abstract: : Ocular involvement in the acute phase of Kawasaki disease typically involves the anterior segment of the eye, and its associated treatment outcomes are generally excellent. However, there are rare reports of posterior segment involvement, and these are associated with poorer outcomes. This study reviewed six patients with recently reported blindness and/or ocular posterior segment involvement in the acute phase of Kawasaki disease. The median age of these patients was 8.5 years old (range: 6-12 years old). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…[19] Previous studies showed that the older children have a risk of non-cardiac complications including arthritis, ocular complications, and AARF during acute phase of KD. [2,3,20] Those findings were consistent with the present study in the patients who received initial IVIG therapy with DUA. Two patients were associated with arthritis in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…[19] Previous studies showed that the older children have a risk of non-cardiac complications including arthritis, ocular complications, and AARF during acute phase of KD. [2,3,20] Those findings were consistent with the present study in the patients who received initial IVIG therapy with DUA. Two patients were associated with arthritis in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Older children may have a higher risk of blindness and ocular posterior segment involvement in the acute phase of KD. [3] Ocular involvement in the acute phase of KD typically involves the anterior segment of the eye, and its associated treatment outcomes are generally excellent. However, there are rare reports of posterior segment involvement, and these are associated with poorer outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations